Ethical risks and considerations of brain-controlled and neuromodulation technologies - Kaifeng Huang; Hengyuan Yang; Shixuan Zhu; Yanxiao Chen; Tianwen Li; Lei Zhao; Anmin Gong; Wenya Nan; Jiaping Xu; Yunfa Fu (Cognitive Neurodynamics, 2026)

Biochar for multi-metal stabilization in smelting soils: Long-term performance and mechanisms under freeze-thaw and dry-wet cycles - Wenchu Zhao; Dongdong Wen; Jiaping Xiong; Zhi Yu; Junlian Qiao; Wei Teng; Rongbing Fu (Environmental Research, 2026)

Microbial abundance shapes latitudinal pattern of the greenhouse gas production potential in blue carbon ecosystems - Lingfang Ni; Chuancheng Fu; Gang Li; Kai Feng; Ye Deng; Jiaping Wu; Carlos M. Duarte; Yuan Li; Dongdong Zhang (Water Research, 2025)

A novel varicosavirus associated with Orychophragmus violaceus in China - Yuanling Chen; Qian Li; Jiaping Yu; Yali Zhou; Shifang Fei; Jianxiang Wu; Shuai Fu (Archives of Virology, 2025)

Why the adventitious roots of poplar are so colorful: RNAseq and metabolomic analysis reveal anthocyanin accumulation in canker pathogens-induced adventitious roots in poplar - Min Li; Yuchen Fu; Jinxin Li; Wanna Shen; Li Wang; Zheng Li; Shiqi Zhang; Huixiang Liu; Xiaohua Su; Jiaping Zhao (Planta, 2025)

A comprehensive review of biodetoxification of trichothecenes: Mechanisms, limitations and novel strategies - Yue Qiu; Jiaping Yan; Aodong Yue; Zhongchao Lu; Jianzhuang Tan; Hong Guo; Yuting Ding; Fei Lyu; Yan Fu (Food Research International, 2024)

Pathological and genome assembly of transcriptome sequencing data implied multiple relationships between bean common mosaic virus (BCMV), Batocera lineolata and aphids in Populus alba var. pyramidalis - Min Li; Jinxin Li; Yanxia Yao; Rui Yang; Yuchen Fu; Li Wang; Wanna Shen; Huixiang Liu; Ya Liu; Jiaping Zhao (Physiological and Molecular Plant Pathology, 2024)

Molar ratio of (-)-epicatechin and (-)-epigallocatechin gallate determined their enzymatic oxidation products and color characteristics - Li Lian; Yuqing Cui; Mingchun Wen; Daniel Granato; Yong-Quan Xu; Yan-Qing Fu; Zongde Jiang; Jiaping Ke; Xiaochun Wan; Liang Zhang (Food Bioscience, 2024)

Efficient ex-vitro rooting and acclimatization for tissue culture plantlets of ginger - Jie Zhou; Fengling Guo; Chuangdong Qi; Jiaping Fu; Ying Xiao; Jinping Wu (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Seasonal dynamics of organic components in fresh foliar litters at different gap positions in an alpine forest on the eastern Tibetan Plateau - Jiaping Yang; Yu Zhang; Changkun Fu; Ziyi Liang; Kai Yue; Zhihong Xu; Xiangyin Ni; Fuzhong Wu (Journal of Soils and Sediments, 2021)

Stocks and losses of soil organic carbon from Chinese vegetated coastal habitats - Chuancheng Fu; Yuan Li; Lin Zeng; Haibo Zhang; Chen Tu; Qian Zhou; Kuanxu Xiong; Jiaping Wu; Carlos M. Duarte; Peter Christie; Yongming Luo (Global Change Biology, 2021)
Global vegetated coastal habitats (VCHs) represent a large sink for organic carbon (OC) stored within their soils. The regional patterns and causes of spatial variation, however, remain uncertain. The sparsity and regional bias of studies on soil OC stocks from Chinese VCHs have limited the reliable estimation of their capacity as regional and global OC sinks. Here, we use field and published data from 262 sampled soil cores and 181 surface soils to report estimates of soil OC stocks, burial rates and losses of VCHs in China. We find that Chinese mangrove, salt marsh and seagrass habitats have relatively low OC stocks, storing 6.3 ± 0.6, 7.5 ± 0.6, and 1.6 ± 0.6 Tg C (±95% confidence interval) in the top meter of the soil profile with burial rates of 44 ± 17, 159 ± 57, and 6 ± 45 Gg C/year, respectively. The variability in the soil OC stocks is linked to biogeographic factors but is mostly impacted by sedimentary processes and anthropic activities. All habitats have experienced significant losses, resulting in estimated emissions of 94.2–395.4 Tg CO 2 e (carbon dioxide equivalent) over the past 70 years. Reversing this trend through conservation and restoration measures has, therefore, great potential in contributing to the mitigation of climate change while providing additional benefits. This assessment, on a national scale from highly sedimentary environments under intensive anthropogenic pressures, provides important insights into blue carbon sink mechanism and sequestration capacities, thus contributing to the synchronous progression of global blue carbon management.

Functional genetic variants in centrosome-related genes CEP72 and YWHAG confer susceptibility to gastric cancer - Jing Ni; Jinchen Wang; Yao Fu; Caiwang Yan; Meng Zhu; Yue Jiang; Jiaping Chen; Yanbing Ding; Xiangshan Fan; Gang Li; Guangfu Jin (Archives of Toxicology, 2020)

In vitro polyploid induction using colchicine for Zingiber Officinale Roscoe cv. ‘Fengtou’ ginger - Jie Zhou; Fengling Guo; Jiaping Fu; Ying Xiao; Jinping Wu (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

The optical properties in alkali-soluble fractions extracted from newly shed litters in a subalpine forest - Jiaping Yang; Yu Zhang; Ziyi Liang; Kai Yue; Changkun Fu; Xiangyin Ni; Fuzhong Wu (Journal of Soils and Sediments, 2020)

Identification of the pathogens causing konjac dry rot in China - Jinping Wu; Jie Zhou; Zhenbiao Jiao; Jiaping Fu; Fengling Guo (Journal of Plant Diseases and Protection, 2019)